Respostas
respondido por:
8
Vamos la:
2x - 4 - 8 = 4x
2x - 4x = 4 + 8
-2x = 12
x = -12/2
x = -6
Espero ter ajudado
2x - 4 - 8 = 4x
2x - 4x = 4 + 8
-2x = 12
x = -12/2
x = -6
Espero ter ajudado
respondido por:
3
2x - 4 - 8 = 4x
2x - 4x = 4 + 8
-2x = 12 (x -1)
2x = -12
x = -12/2
x = -6
Espero ter ajudado
2x - 4x = 4 + 8
-2x = 12 (x -1)
2x = -12
x = -12/2
x = -6
Espero ter ajudado
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
2x - 4x = 4 + 8
-2x = 12
x = -12/2
x = -6
Espero ter ajudado